Adaptabilidade e estabilidade fenotípica de linhagens de algodoeiro herbáceo para as condições do semiárido nordestino - Silva, Ruan dos Santos (2019)
Upland Cotton (Gossypium hirsutum L.) is one of the most important fiber producing crops. Brazil stands out on the world stage as one of the main producers and exporters of cotton fiber. The planting of this crop in the brazilian semiarid region is important for the regional development and increase of the competition capacity of the Northeast cotton farmer. Thus, the development of breeding programs that identify cultivars adapted to the conditions of the region is fundamental. In conducting these programs, the study of genotypes x environments interaction before selection and recommendation of cultivars help in choosing and indicating the best materials. In this context, the objective of this study was to evaluate the genotypes x environments interaction of final lines of upland cotton, in order to identify adapted and stable genotypes for the northeastern semiarid conditions. Seventeen genotypes were evaluated in experiments conducted in the cities of Apodi-RN and Barbalha-CE in 2016 and 2017, totaling four environments. The characteristics evaluated were: cotton seed yield, cotton fiber yield, lint percentage, fiber length, fiber strength, micronaire and spinning index. Individual and joint analyzes of variance were performed. The adaptability and stability analyzes was evaluated following the methodologies proposed by Eberhart and Russell (1966), Lin and Binns (1988) modified by Carneiro (1998), Annicchiarico (1992) and GGE Biplot (2000). The different methodologies adopted in this study were concordant and complementary, being efficient and easily applied in the identification of adapted and stable cotton genotypes. The results indicated the genotypes CNPA NE 2012-2050, CNPA MT 2009-152, CNPA NE 2012- 2008 and CNPA BA 2011-4970 FL as the most productive, and more adaptability for the evaluated region. CNPA BA 2011-4436, CNPA BA 2011-1197 and CNPA BA 2010-1174 also presented productive potential and were considered the most stable.